Expression of HMA4 cDNAs of the zinc hyperaccumulator Noccaea caerulescens from endogenous NcHMA4 promoters does not complement the zinc-deficiency phenotype of the Arabidopsis thaliana hma2hma4 double mutant - Iqbal, Mazhar; Nawaz, Ismat; Hassan, Zeshan; Hakvoort, Henk W.; Bliek, Mattijs; Aarts, Mark G.; Schat, Henk (Frontiers in Plant Science, 2013)
Noccaea caerulescens (Nc) exhibits a very high constitutive expression of the heavy metal transporting ATPase, HMA4, as compared to the non-hyperaccumulator Arabidopsis thaliana (At), due to copy number expansion and altered cis-regulation. We screened a BAC library for HMA4 and found that HMA4 is triplicated in the genome of a N. caerulescens accession from a former Zn mine near La Calamine (LC), Belgium. We amplified multiple HMA4 promoter sequences from three calamine N. caerulescens accessions, and expressed AtHMA4 and different NcHMA4 cDNAs under At and NcHMA4 promoters in the A. thaliana (Col) hma2hma4 double mutant. Transgenic lines expressing HMA4 under the At promoter were always fully complemented for root-to-shoot Zn translocation and developed normally at a 2-μM Zn supply, whereas the lines expressing HMA4 under Nc promoters usually showed only slightly enhanced root to shoot Zn translocation rates in comparison with the double mutant, probably owing to ectopic expression in the roots, respectively. When expression of the Zn deficiency responsive marker gene ZIP4 was tested, the transgenic lines expressing AtHMA4 under an NcHMA4-1-LC promoter showed on average a 7-fold higher expression in the leaves, in comparison with the double hma2hma4 mutant, showing that this construct aggravated, rather than alleviated the severity of foliar Zn deficiency in the mutant, possible owing to expression in the leaf mesophyll.